From Fiqh to Political Advocacy: Muhammadiyah’s Ecological Movement in the Post New Order Indonesia - Efendi, David; Kurniawan, Nanang Indra; Santoso, Purwo (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2021)
This paper investigates how Indonesia’s Islamic modernist movement, Muhammadiyah, is responding to issues such as environment degradation, global warming and climate change. Muhammadiyah has not adopted the ecology paradigm used by Islamic environmentalism group, focusing instead on theological reform and social and economic welfare and justice, but members of its elite have begun inserting ecological concerns into the organisation’s programmatic orientation. This paper argues that, although these efforts are not well organized and maintained, they have enormous potential to transform Muhammadiyah into a right-green organization, as demonstrated through its progressive initiative on the environment and its efforts institutional and theological reform (fiqh of water) and in its involvement in judicial review of state policy (known as ‘jihad konstitusi’/judicial review) as political advocacy practice. However, the main feature of Muhammadiyah’s environmental activism is its continued emphasis on economic justice rather than on building ecological security and conservation movement.